Collaboration and Multi-Stakeholder Engagement in Landscape Governance and Management in Africa: Lessons from Practice - Shackleton, Sheona; Favretto, Nicola; Gordon, Chris; Methner, Nadine; Outa, George; Sola, Phosiso; Sallu, Susannah; Sikutshwa, Likho; Williams, Portia Adade (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The severity of interconnected socio-economic and environmental impacts on landscapes and people across Africa are exacerbated as a result of land degradation, conflict, poor governance, competition for land and inequality, and exacerbated by climate change. In pursuing pathways towards a more resilient future, collaborative and multi-stakeholder governance and management of landscapes have been promoted by government agencies, NGOs and conservation organisations as a possible solution. However, there is no single way to achieve effective collaboration, and different landscape projects have experimented with different entry points and engagement processes. Grounded in partnerships amongst researchers, practitioners and development partners with expertise in landscape governance and management in Africa, this book describes and collates key lessons from practice for supporting more resilient and equitable landscapes.